Efficacy and safety of first-line immune checkpoint inhibitor combination therapies in patients with advanced esophageal squamous cell carcinoma: a network meta-analysis - Wang, Chenglong; Cai, Tongze; Wei, Jiangcun; Huang, Ying; Xiao, Lin (Frontiers in Oncology, 2024)
BackgroundWe performed a network meta-analysis of phase III trials to compare the efficacy and safety of first-line regimens for patients with advanced esophageal squamous cell carcinoma (ESCC).MethodsA systematic review and Bayesian network meta-analysis were conducted by retrieving relevant literature from PubMed, Embase, the Cochrane Library, and the Web of Science. We included published sources of randomized clinical trials comparing immunotherapy combinations for treating advanced ESCC.ResultsWe analyzed seven studies involving eight immunotherapy combinations and 4688 patients. For patients without programmed death-ligand 1 (PD-L1) selection, it was found that the combination of toripalimab and chemotherapy provided better overall survival than chemotherapy alone (hazard ratio = 0.58, 95% confidence interval (CI) 0.43-0.78). Compared with chemotherapy alone, Sintilimab or camrelizumab plus chemotherapy seemed to achieve the best progression-free survival (hazard ratio = 0.56, 95% CI 0.46-0.68). Nivolumab plus chemotherapy appeared to provide the best objective response rate, with significant differences versus chemotherapy alone (odds ratio = 0.49, 95% CI 0.38-0.64). Nivolumab plus ipilimumab resulted in a relatively lower incidence of adverse events of grade ≥3 than other regimens.ConclusionsThe combination of immune checkpoint inhibitors (ICIs) with chemotherapy provided a high probability of more effective treatment in comparison with chemotherapy alone for patients with advanced ESCC. Toripalimab and sintilimab plus chemotherapy were ranked as providing the highest OS and PFS benefit in the first-line setting, respectively.